Wheat and soybean productivity on a Dark Red Latosol due to simulated and rainfall erosion - Gaertner, Carlos (2003)
The objective of this work was to evaluate the effect of erosion simulated by removal of surface soil layers and the effect of rainfall erosion on wheat and soybean productivity. Thickness of soil layers removed artificially to simulate erosion effects were 0 cm, 3 cm, 6 cm and 14 cm, representing the entire Ap horizon. Wheat productivity did not allow to establish any correlation with thickness of removed soil. The reduction of soybean productivity was 148 kg ha-1 and 105 kg ha-1 per cm of soil removed, in 0 to 6 cm and 0 to 14 cm layers, respectively. Cation exchange capacity and Ca+Mg content, in different soil depth, were the soil attributes that most influenced soybean productivity. Organic carbon content was the only soil attribute to correlate with soybean and wheat yields, in both, rainfall and simulated erosion conditions. Simulation of erosion effect on soybean yield by removal of different soil surface layers can be used, once the difference on soybean productivity compared to the same soil layer lost by natural erosion was less than 6%.